Enchancing anaerobic endurance across soccer player postions through high intensity interval training - Sahrur Ramadhan; Dikdik Zafar Sidik; Fitri Rosdiana; Ira Purnamasari (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to examine the effect of the High Intensity Interval Training method on improving the anaerobic endurance of soccer players based on their playing positions: Goalkeeper, Defender, Midfielder, and Striker. The research employed a quasi-experimental method with a one-group pretest-posttest design. The sample consisted of four soccer athletes, each representing a different playing position. The High Intensity Interval Training program was carried out over a period of four weeks with a training frequency of twice per week. Anaerobic endurance was measured using the Running-based Anaerobic Sprint Test (RAST) both before and after the intervention. The data from the pre-test and post-test were analyzed using a paired t-test. Analysis using SPSS version 23 revealed a statistically significant improvement in the anaerobic endurance of the soccer players after participating in the High Intensity Interval Training program, with a significance value of 0.023 (p < 0.05). These findings support the effectiveness of the High Intensity Interval Training method as an efficient physical training approach to enhance the anaerobic component of soccer athletes across various playing positions.